Folate, neopterin and kynurenine pathway in patients with statin therapy - Palabıyık, Şaziye Sezin; Gi?rgi?n, Gözde; Aşçi, Ali; Demirelli, Selami; Uslu, Abdulkadir; Karakelleo?lu, Şule; Akçay, Fatih (Walter de Gruyter GmbH, 2016)
Statins, widely used antihyperlipidemic drugs, also have immunomodulatory properties independent from their lipid lowering effect. Even with slight modulations in the immune system, pteridine levels can display changes. The effect of statins on pteridines and related pathways has been demonstrated in a limited number of studies. The aim of the study was to evaluate the possible changes in neopterin and folate levels, and tryptophan (Trp) degradation in hyperlipidemic patients. Patients who were admitted to the cardiology clinic were randomly grouped if they were having statin treatment (n=69) or not (n=36). Serum Trp and kynurenine (Kyn), erythrocyte folate, and urinary neopterin levels were measured. It was found that urinary neopterin levels were significantly higher in patients on statin treatment (p<0.05) while levels of folate, Trp, Kyn, and Kyn-to-Trp ratios (Kyn/Trp) presented no significant changes (all, p>0.05). The correlation of the measured parameters was also evaluated and neopterin, folate and tryptophan degradation were found to be positively correlated. According to the results, neopterin levels, folate status and Trp degradation were altered in patients with statin treatment in comparison with the patients not receiving statin therapy. In order to point out the direct effect of statins on pteridines, further studies presenting both pre-and post-statin treatment of these parameters are needed. © 2016 by De Gruyter.
Keywords: folate; kynurenine; neopterin; statin; tryptophan